2006
DOI: 10.1007/s10592-006-9165-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the capercaillie in Eurasia: what is the conservation status in the Pyrenees and Cantabrian Mounts?

Abstract: International audienceThe Western capercaillie (Tetrao urogallus) is a keystone species of Palearctic boreal and altitude coniferous forests. With the increase of mountain leisure activities and habitat loss, populations are declining in most mountain ranges in Western Europe. Recent work has shown that the populations from the Pyrenees and Cantabrian Mountains survived a severe bottleneck during the 19th century, and are still considered as threatened due to habitat fragmentation and isolation with other popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
3
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 51 publications
9
81
3
3
Order By: Relevance
“…This suggests that the division of the Polish population might be more long-lasting. A strong genetic structure in the Polish population corresponding to geographical regions is also surprising given the mitochondrial phylogeography of the capercaillie [66,75,76], which shows that boundaries of morphological subspecies correspond rather weakly to genetic differentiation.…”
Section: Estimation Of Genetic Variability and Genetic Differentiatiomentioning
confidence: 99%
“…This suggests that the division of the Polish population might be more long-lasting. A strong genetic structure in the Polish population corresponding to geographical regions is also surprising given the mitochondrial phylogeography of the capercaillie [66,75,76], which shows that boundaries of morphological subspecies correspond rather weakly to genetic differentiation.…”
Section: Estimation Of Genetic Variability and Genetic Differentiatiomentioning
confidence: 99%
“…Patterns of postglacial dispersal from refugia in the southern peninsulas of Iberia, Italy and the Balkans have been described for several species, such as bears, voles, oaks (see Taberlet et al 1998) and Capercallie (Duriez et al 2007;Segelbacher and Piertney 2007). Other taxa such as Black Grouse did not follow this pattern (Bilton et al 1998).…”
Section: Postglacial Colonisationmentioning
confidence: 96%
“…This was refuted by Schreiber et al (1998) in an analysis of 38 allozyme loci in 95 individuals from southern Germany, Netherlands and Sweden. Subspecies were often described on the basis of a few skins kept in museums, in which colours can change with the age of the bird and the time since collection, and the skeleton was not necessarily available (Duriez et al 2007). These taxonomic divisions need to be revised in order to assess, design and implement conservation plans for a species or subspecies (Mace 2004).…”
Section: Species Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…On local and regional scales, many populations of grouse are declining, particularly in densely populated and intensively used landscapes (Storch, 2000). Two recent studies on capercaillie phylogeography have shown that the cantabrian capercaillie (Tetrao urogallus cantabricus) has a high level of genetic differentiation in relation to the rest of the capercaillie subspecies (Duriez et al, 2007;Rodríguez-Muñoz et al, 2007). This is also the only capercaillie subspecies adapted to live in pure deciduous forests and qualifies as Endangered under IUCN criteria (Storch et al, 2006).…”
Section: Cracidsmentioning
confidence: 99%